Activities for developing creative reading among grade three fast learners - Gordove, Emilie Garlit 1939- (College of Education, University of the Philippines Diliman, 1976)
The purpose of the study is to present activities designed to facilitate creative reading among Grade Three fast learners using stories from the basal and supplementary readers for Grade Three classes in the public schools. The activities used to facilitate creative reading were patterned after those suggested by Torrance. All the lessons were tried out for two consecutive weeks with 27 fast learners in Grade Three in the Jose Rizal Elementary School, Pasay City. Excerpts from the try-out of the lessons showing some of the pupil's responses indicate that creative reading can be facilitated among Grade Three fast learners using specific techniques and available reading materials.